Formasi Ideologi Dalam Novel Ksatria, Putri, Dan Bintang Jatuh Karya Dee Lestari - Maymanah, Qathrunnada; Priyadi, Antonius Totok; Wartiningsih, Agus (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
The purpose of this research is to ascertain the findings of the examination of the ideology creation in Dee Lestari's book Ksatria, Putri, dan Bintang Jatuh. Formal and descriptive qualitative methodologies were used to ensure the quality of this study. This study employs sociological and objective methods. Supernova: Ksatria, Putri, dan Bintang Jatuh by Dee Lestari serves as the research's primary source of data. Quotations from fresh lines that lead to the subject of analysis are used in the study. methods for gathering data while using documentary research methods. Three methods are used to assess the validity of the data: referential coverage, persistence, and triangulation. The results of this study are an ideology consisting of conservatism, liberalism, theism, pantheism, and new age. the result of the ideology formation are the conservatism collaborates with theism, liberalism collaborates with pantheism, pantheism collaborates with new age, new age collaborates with liberalism, liberalism incompatible with conservatism, liberalism incomplatible with theism, theism incompatible with pantheism, theism incompatible with new age.